English-majored Students’ Perceptions of Their Autonomy in English Language Learning - Nguyen, Giang Thi Tuyet; Nguyen, Thuong Thi Kim (EDUPEDIA Publisher, 2024)
Learner autonomy is not a new concept in education as it is one of the important goals set for students in any language curriculum, especially when most universities in Vietnam employ a credit-based system that requires students to take more responsibility for their learning. The ability to learn autonomously is considered to be an indispensable and important attribute of a successful language learner. This mixed-method study, hence, aimed to explore English-majored students' perceptions of their responsibilities and identify the key factors influencing their autonomy in English learning. The analysis of the quantitative data revealed that the majority of students perceive themselves as autonomous learners, demonstrating a willingness to take responsibility for their English language learning both inside and outside of the classroom. Besides, the findings reveal that various factors influence autonomous English learning, including a lack of motivation, a lack of learning strategies, and laziness. Some possible solutions suggested through the semi-structured interview involve improving self-regulating skills, strengthening student-student and student-teacher interactions, and getting more support from university officials and others in society. Finally, there were pedagogical implications for developing learner autonomy during the process of English teaching and learning.